Perlindungan Hukum terhadap Anak Korban Kekerasan Seksual - Yuliartini, Ni Putu Rai; Mangku, Dewa Gede Sudika (Universitas Negeri Malang, 2021)
This study aimed to analyze the implementation of legal protection for child victims of sexual violence in Singaraja City and the efforts of law enforcement officials in reducing the number of sexual violence in Singaraja City. This study used an empirical legal research approach with a descriptive type. Sources of data were obtained from primary data and secondary data. Data collection techniques through observation, interviews, and documentation studies. Determining the sample uses a non-probability sampling technique called purposive sampling. The data is processed and analyzed qualitatively. The results study indicated that the implementation of legal protection for child victims of sexual violence in Singaraja City had not run optimally. Some several facilities and services had not been fulfilled. The Buleleng Police took preemptive, preventive, and repressive measures to reduce the number of sexual violence in Singaraja City. The Social Service of Buleleng Regency assisted in assistance, trauma recovery, and counseling services for children who were victims of social violence.